How Does Greenery on a Nearby Façade Change Perception of a Window View? - Samo Drobne; Martina Zbašnik-Senegačnik; Živa Kristl; Ljudmila Koprivec (Prostor, 2022)
Window view is an important parameter of living comfort. In densely urbanized areas, window view is often limited to the nearby façade, without all three visual layers visible and possibility of distant view. The purpose of the study is to examine what reactions are triggered by views of nearby façades, which by definition are not quality window views, and how the reactions of observers are influenced by additional greenery on the façade. A questionnaire survey was used in the study as a method for obtaining research data. Respondents defined reactions to 20 various window views and the reasons for them. The results showed that reactions to window views of nearby façades varied, and that the negative response depended not only on a limited number of visual layers and the distance between buildings, but also on visual aesthetic.Furthermore, added greenery in the window view triggered more positive reactions than did façades without greenery. Measures for greening façades are proposed.